1982
DOI: 10.1007/bf00403734
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of the development of benzopyrene-induced skin cancer in mice by microwave radiation

Abstract: Development and growth of skin cancer may be affected by various physical and chemical factors present in human environment. Of these factors electromagnetic radiation of radio- and microwave spectra are among the most common. In the present study Balb/c mice were exposed to chemical carcinogen, 3,4-benzopyrene, painted on the skin every 2nd day for a total of 6 months, and simultaneously irradiated with athermal (5 mW/cm2) or subthermal (15 mW/cm2) doses of 2,450 MHz microwaves. The other group of animals was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…These include the possibility of initiation and/or promotion of carcinogenesis and the induction of genetic damage (WHO, 1993). Some studies indicated that exposure to radiofrequencies promoted cancer in conventional mice and lymphoma in transgenic mice (Em-pim 1) that are prone to lymphoma (Szmigielski et al, 1982;Szudzinski et al, 1982;Repacholi et al, 1997). However, Sommer et al (2004) showed that mobile phone exposure does not promote lymphoma in AKR/J mice.…”
Section: Introductionmentioning
confidence: 94%
“…These include the possibility of initiation and/or promotion of carcinogenesis and the induction of genetic damage (WHO, 1993). Some studies indicated that exposure to radiofrequencies promoted cancer in conventional mice and lymphoma in transgenic mice (Em-pim 1) that are prone to lymphoma (Szmigielski et al, 1982;Szudzinski et al, 1982;Repacholi et al, 1997). However, Sommer et al (2004) showed that mobile phone exposure does not promote lymphoma in AKR/J mice.…”
Section: Introductionmentioning
confidence: 94%
“…The new calculated permittivity for E + D at 42 GHz is ε m = 15-j20.5. In the simulation, based on the statistic data, the thickness of SC is changed to around 50 μm [18].…”
Section: Skin Modelmentioning
confidence: 99%
“…The evidence of radiofrequency radiation carcinogenesis has increased since 2011. Some animal studies suggest that exposure to electromagnetic fields accelerate the development of sarcoma colonies in the lung, mammary tumors, skin tumors, hepatomas, and sarcomas [21,22]. This study detected an increase in the rate of death by cancer in capitals where there is a greater exposure to electromagnetic fields emanating from radio base stations.…”
Section: Discussionmentioning
confidence: 51%